Epigenetic treatment of pancreatic cancer: is there a therapeutic perspective on the horizon?. Issue 1 (3rd November 2016) - Hessmann, Elisabeth; Johnsen, Steven A; Siveke, Jens T; Ellenrieder, Volker
Abstract : Pancreatic ductal adenocarcinoma (PDAC) constitutes one of the most aggressive malignancies with a 5-year survival rate of <7%. Due to growing incidence, late diagnosis and insufficient treatment options, PDAC is predicted to soon become one of the leading causes of cancer-related death. Although intensified cytostatic combinations, particularly gemcitabine plus nab-paclitaxel and the folinic acid, fluorouracil, irinotecan, oxaliplatin (FOLFIRINOX) protocol, provide some improvement in efficacy and survival compared with gemcitabine alone, a breakthrough in the treatment of metastatic pancreatic cancer remains out of sight. Nevertheless, recent translational research activities propose that either modulation of the immune response or pharmacological targeting of epigenetic modifications alone, or in combination with chemotherapy, might open highly powerful therapeutic avenues in GI cancer entities, including pancreatic cancer. Deregulation of key epigenetic factors and chromatin-modifying proteins, particularly those responsible for the addition, removal or recognition of post-translational histone modifications, are frequently found in human pancreatic cancer and hence constitute particularly exciting treatment opportunities. This review summarises both current clinical trial activities and discovery programmes initiated throughout the biopharma landscape, and critically discusses the chances, hurdles and limitations of epigenetic-based therapy in future PDAC treatment.